DETERMINANTS OF EXPORT COMPETITIVENESS OF AGRICULTURAL PRODUCTS IN MALAYSIA - Liew, Siew Ling; Mohammad Affendy, Arip; Puah, Chin Hong (UNIMAS Publisher, 2021)
This study intends to evaluate the export competitiveness of agricultural products using the data of 186 agricultural commodities in Malaysia for the period ranging from 1988 to 2014. Besides, this study engages in the total export of the world with Standard International Trade Classification Revision Three-SITC Revision 3 (5-digits code) to analyse the index of comparative advantage of agricultural commodities in Malaysia. In addition, the study employs Balassa (1965) index of Revealed Comparative Advantage (RCA) to measure competitiveness. The findings show that 56 commodities have comparative advantage. Apart from that, this study also empirically examines the determinants of competitiveness which are commodities price, GDP per capita, labour participation and capital formation. The results of cointegration tests estimation indicates that there is a long-run relationship between the variables under study. The outcomes denote that price of commodities, GDP per capita and crises in 2008 have negative association while labour participation and capital formation are positively relatedly to competitiveness. The results also specify that there is a short-run dynamic impact on competitiveness with the variables. This study suggests that the government should consider intensifying the current economic policy through focusing on downstream products by taking the benefit of its comparative advantage in upstream industries to increase competitiveness.